Optimizing the Use of Online Systems in Health Care Facilities - Aprilano, Wendy Damar; Nadjib, Mardiati (UI Scholars Hub, 2024)
The use of web-based information technology or online services can accelerate service delivery. Digitalisation of online health services is one of the growing issues, along with the increasing need for access to health services globally. However, there are things that must be considered in implementing an online health service system so the utilisation can be optimal. This study examines the factors that can support the optimisation of online service systems in health facilities so that innovation can continue to grow and provide benefits in the future. The authors conducted a literature review, with PRISMA guidelines according to the PEO (Population, Exposure, Outcome) method with a population focus on health facilities that use online health registration and service systems, both applications and web, and the success factors of using existing online systems when applied to users. A total of 607 articles were searched, and after selection, 22 articles fulfilled the inclusion criteria and research objectives. Analysis of each article illustrated that optimising online systems in healthcare should be fully integrated into clinical workflows and add value to patient care while offering easier processes and facilitating communication between healthcare services. User and provider engagement is also important in the development of online healthcare systems. It also needs to be supported by various parties, from the government to the healthcare provider level. Ultimately, optimising online systems in healthcare is very useful in effectively cutting down service delivery time to improve the quality of healthcare and health status in the future.